Knowledge about HIV and syphilis serologic status among sex workers from Pelotas, Brazil - Silveira, Mariângela F.; Alves, Cíntia L.; Brum, Vera Maria A.; Teixeira, Ana Maria F.B.; Rosenthal, Renata M.; Stauffert, Dulce (Brazilian Journal of Sexually Transmitted Diseases, 2009)
Introduction: sex workers are more vulnerable to syphilis and HIV. Knowledge about serologic status allowed treatment and prevention behaviors. Objective: to evaluate the knowledge of sex workers from Pelotas/RS about their serologic status for syphilis and HIV. Methods: cross-sectional study population based, descriptive, done in 2006, with 322 sex workers aged 18 years old or more. A questionnaire about knowledge of syphilis and HIV serologic status was applied and we did rapid test for syphilis. Results: most of the interviewed were female (76.1%), between 22-39 years (64.9%), white skin (63.7%), schooling between 5-8 years (45.7%), 57.5% had never been tested for syphilis. Among those tested, 19.6% had a positive test, 65% went to public laboratories, and the most common reason was antenatal care, syphilis rapid test was positive for 24 people. 88% had already been tested for HIV. Most frequent reasons for this test were “I think I have risk”, “precaution”, “control” (27%) and antenatal care (24%). Seventeen sex workers already knew being HIV+ and 13 were under clinical care. Conclusion: percentage of syphilis testing among the interviewed was low. More frequent HIV testing may be related to the greater knowledge about this disease. Public laboratories are the main place for testing and antenatal care is a common reason for the exams. Many of the interviewed realized the test because recognized being at risk